COVID-19 and childhood obesity (CO-BESITY) in the era of new normal life: A need for a policy research - Sudip Bhattacharya; Pradeep Agarwal; Om Prakash Bera; Sheikh Mohd Saleem; Deep Shikha; Vidisha Vallabh; Ruchi Juyal; Amarjeet Singh (SAGE Publishing, 2021)
Background: In the era of new normal life (after Coronavirus Disease 2019 (COVID-19)), our children are experiencing the double threat of COVID-19 and Childhood Obesity (CO-BESITY). The rate of childhood obesity has been rapidly increasing in developed as well as low middle-income countries during the pandemic. Design and Methods: The current paper aims to identify the probable reasons of increase in childhood obesity during this pandemic and offers suggestions to reduce the burden of it. Literature search was done using PubMed, Google Scholar, and Scopus databases for the key terms "childhood obesity," "obesity," "pandemic," and/or childhood obesity. All the relevant articles were included to support the argument for this viewpoint. Results: Childhood obesity is a complicated disorder having diverse outcomes. The incidence of childhood obesity is clearly analysed from Bronfenbrenner's model of child development. The model examines an overabundance of bio-psycho-social backgrounds, risks, and probable outcomes on the development of a child. COVID-19 pandemic has disrupted the ecosystem of this dynamic model and has created an economic and social-cultural crisis that has ignited a chain reaction of stressors upon children and their families. In this paper, we have described how this Bronfenbrenner's model of child development also known as the Bioecological Model can be effective for the estimation and prevention of childhood obesity. Conclusion: We propose that this Bioecological Model will help the children and their families further to understand and manage the problem of childhood obesity during this pandemic on their own.